PELATIHAN ON-LINE PEMBUATAN PERANGKAT HAND SANITIZER BERBAHAN NON-ALKOHOL PADA PEMUDA BINAAN - Mochamad Lazuardi; Hani Plumeriastuti; Eka Pramyrtha Hestianah (Universitas Airlangga, 2020)
Training on non-alcohol based hand sanitizer (HS) was conducted for assisted youth in five districts, namely Gresik, Bojonegoro, Lamongan, Probolinggo and Nganjuk for three days. In the training, competency strengthening was carried out, namely theory and practicum, ending with evaluation of activities. During the implementation of theory and practicum, training materials were provided using social media facilities in the form of WhatsApp and e-mail. Specifically for coordination with participants, a training group was created using social media. The results of the training evaluation turned out that in terms of strengthening the competence of knowledge in making HS and working mechanisms of HS, it was increasing. In terms of straightening the meaning of HS production to be more focused according to the basis of science or good manufacturing practices (GMP). Thus, youth assisted with criteria include youth who are able to pass on knowledge to all young people in their respective districts. Furthermore, the knowledge and skills of the assisted youth in making HS based on non-alcoholic substances will be more agile and targeted. Thus, in reality, the training on making non-alcohol based HS has made the assisted youths become pioneers at the end of the line to pass on their knowledge. The conclusion in the implementation of this training is that the assisted youth are capable and ready to make non-alcohol-based HS as well as being ready to produce for a small scale while showing real work to be transmitted (98%). abstrakTelah dilakukan pelatihan pembuatan hand sanitizer (HS) berbasis non-alkohol terhadap pemuda binaan di lima kabupaten yaitu Gresik, Bojonegoro, Lamongan, Probolinggo dan Nganjuk selama tiga hari. Dalam Pelatihan tersebut dilakukan pemberian penguatan kompetensi yaitu teori dan praktikum diakhiri dengan evaluasi kegiatan. Selama berlangsung pelaksanaan teori dan praktikum, materi pelatihan diberikan menggunakan fasilitas media sosial berupa whatsapp dan e-mail. Khusus koordinasi dengan peserta dilakukan pembuatan grup pelatihan menggunakan media sosial. Hasil evaluasi pelatihan ternyata dari segi penguatan kompetensi pengetahuan pembuatan HS dan mekanisme kerja HS, makin meningkat. Segi pelurusan pengertian produksi HS menjadi makin terarah sesuai basis ilmu pengetahuan atau cara pembuatan obat yang baik (CPOB). Dengan demikian pemuda binaan dengan kritetria termasuk pemuda yang sanggup menularkan ilmu ke seluruh masyarakat muda di kabupaten masing-masing. Lebihlanjut pengetahuan dan ketrampilan pemuda binaan dalam membuat HS berbasis bahan non-alkohol makin cekatan dan terarah. Dengan demikian seacara nyata pelatihan pembuatan HS berbasis non-alkohol telah menjadikan pemuda binaan sebagai pelopor di ujung garis untuk menularkan ilmunya. Kesimpulan dalam pelaksanaan pelatihan ini adalah para pemuda binaan telah sanggup dan siap membuat HS berbasis non-alkohol sekaligus siap berproduksi untuk skala kecil sambil memperlihatkan karya nyata untuk ditularkan (98 %).